International Portfolio Investment. The Case of Central and Eastern European Countries - Mrzygłód, Urszula; Adamska-Mieruszewska, Joanna (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The literature on the investment portfolio is dominated by the problem of investment flows to developing countries and emerging markets (portfolio inflows). The problem of developing and emerging countries acting as investors on the international financial markets has been explored to the less extent. This paper is devoted to the analysis of portfolio investments held by residents of the states of Central and Eastern Europe.